Endemic Poverty and the Challenges of Peace and Development in Africa - Ojo, Mathew O. (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
This study seeks to explore the nexus between the alarming rate of poverty and developmental retardation with the attendant implications for peace and security in various independent states of Africa. Using descriptive method of data collection, the study identifies that failure of successive governments in various countries on the continent to creatively address the problem of poverty through purpose-driven policy responses has invariably posed devastating threats to the search for durable peace, and hindered the quest for sustainable development on the continent. In corollary, Africa’s slow pace of development accounts for the continued intensity of poverty, thereby impacting negatively on peace and security. Therefore, the study contends that efforts at ensuring stable peace, which is the bedrock of sustainable development, can only yield the desired fruition ifholistic approach is designed for addressing the menace of poverty afflicting the continent and its people. In the final analysis, the study offers recommendations towards ensuring peace and development with a view to preventing endemic poverty confronting the continent and its citizenry.